Makers : the new industrial revolution. - Anderson, Chris, 1961- (New York : Crown Business, 2012)
What happens when DIY meets Web 2.0? In Makers, New York Times bestselling author Chris Anderson reveals how entrepreneurs use web principles to create and produce companies with the potential to be global in scope as well as how they use significantly less in the way of financial resources, tooling, and infrastructure required by traditional manufacturing. Anderson's unique perspective is that small manufacturing will be a significant source of future growth; that the days of giant companies like General Motors are in their twilight; that in an age of open source, custom-fabricated, and do-it-yourself product design, the collective potential of a million garage tinkerers will be unleashed on global markets.